2020
DOI: 10.1097/scs.0000000000006077
|View full text |Cite
|
Sign up to set email alerts
|

Using Dehydrated Amniotic Membrane Skin Substitute in Facial Burns: Is There a Outcome Difference Between Adult and Pediatric Patients?

Abstract: Introduction: Facial burns have significant physical and psychological effects on patients, and minimizing morbidity continues to be a challenge for reconstructive surgeons. Advancements have allowed the development of various skin substitutes. Among these, human dehydrated amniotic skin substitutes represent novel technology, yet their outcome has not been sufficiently studied to guide practice. The objective of our study is to compare the safety of amniotic membrane skin substitutes in the treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…Regarding the reasons for the differences in preoperative anxiety scores at different ages, it can be seen from previous studies that with the increase of age, the psychological endurance of individuals is continuously improved, and the psychological emotions expressed in medical operations are also significantly different. This confirms the lower anxiety scores of older children in the present study (24,25).…”
Section: Discussionsupporting
confidence: 90%
“…Regarding the reasons for the differences in preoperative anxiety scores at different ages, it can be seen from previous studies that with the increase of age, the psychological endurance of individuals is continuously improved, and the psychological emotions expressed in medical operations are also significantly different. This confirms the lower anxiety scores of older children in the present study (24,25).…”
Section: Discussionsupporting
confidence: 90%
“…A study showed paediatric facial burns treated with hAM had a higher incidence of dyspigmentation relative to adult patients (46.2% versus 9.1%, P ≤ 0.05) 25 . 19.…”
Section: Methodsmentioning
confidence: 99%
“…f. The duration of hAM application in wounds: AM dressings can be changed till the red granulation tissue is replaced by a pale epithelial layer. g. Type of wounds/ defects: Most of the studies were on paediatric second and third-degree paediatric thermal burn 11,26,25,38 . Six studies on congenital birth defects (meningomyelocele) were identified in which, one study showed antenatal inutero repair and four were of postnatal repair 14,39,13 .…”
Section: E Frequency Of Dressing Change In Woundsmentioning
confidence: 99%
“…To date, the hAM has been broadly applied in clinical procedures, including gynecology [ 136 ], ophthalmology [ 137 ], neurosurgery [ 138 ], plastic surgery [ 139 ], gastrointestinal surgery [ 140 ], and orthopedics [ 141 ], as well as wound dressing for burns, or the acute and chronic wounds [ 121 , 142 ]. The clinical applications of hAM also have been reviewed in many publications [ [143] , [144] , [145] , [146] ]. These articles have investigated unmodified hAM applications.…”
Section: Applications Of Ham and Its Composites In Tissue Engineeringmentioning
confidence: 99%